A new striped species of Brachychalcinus (Ostariophysi: Characiformes) from Amapá and Pará states, northern Brazil - Garcia-Ayala, James Raul [UNESP]; de Lima, Flávio César Thadeo; Gama, Cecile de Souza; Benine, Ricardo Cardoso [UNESP] (FapUNIFESP (SciELO), 2024)
A new species of Brachychalcinus is described from the rio Mapaoni, rio Jari basin, and the coastal rio Araguari, Amapá and Pará states, Brazil. The new species is distinguished from all congeners, except B. reisi, by possessing conspicuous longitudinal dark stripes across the body. It can be diagnosed from B. reisi by having longer predorsal and preanal spines, by having scales with few curved radii, and by having more scale rows between lateral line and midventral scale series. A single specimen from rio Tapajós (Pará, Brazil) bears all the diagnostic features of the new species and is herein tentatively identified as belonging to this taxon, extending its distribution to this river basin.
Keywords: Brachychalcinus reisi; Color pattern; Freshwater fishes; Stethaprioninae; Taxonomy